British local authority planners, planning reform and everyday practices within the state. (January 2022) - Clifford, Ben
Reform of the planning system, and the local authority context in which it operates, has been high on the political agenda for all governments in the United Kingdom in the 21st century, reflecting common broader international trends under New Public Management and neoliberalism. Whilst such reforms have been subject to a great deal of academic attention, much of this work has focused on central government perspectives and understands these reforms based on policy documents and Ministerial statements. Whilst revealing important contextual, ideological and intentional imperatives, such perspectives can overlook the way in which reforms are mediated by frontline professionals as they implement them. Drawing on extensive empirical data with British local authority planners considering their reaction to a host of recent reform initiatives such as changes to plan-making, performance targets, austerity and deregulation of planning controls, this paper outlines the importance of a focus on this everyday scale of governance. Arguing for a decentred approach, understanding the situated agency of professional planners, the paper concludes that policy implementation remains a messy process and that notions of professional identity and narratives about what it means to be a 'good planner' remain important in understanding reform specifically and 'the state' more generally.